Rethinking age in athletic retirement: An existential-narrative perspective - Ronkainen, N. J.; Ryba, T. V. (International Journal of Sport and Exercise Psychology, 2017)
The aim of this paper is to examine theoretical understandings of athletic career and career termination from an existential-narrative perspective. Our critical analysis suggests that career models and many research texts have an implicit understanding of sport as a profession and propose a normative end to the career when athletes no longer improve their results. Being framed by Western cultural narratives of ageing as decline, the aforementioned career models disregard athletes` subjective careers and their agency in bringing meaning to experiences of ageing and decline in athletic performance. While the main focus of this paper is on theoretical analysis, some empirical findings from our recent life story research are offered to illustrate alternative narratives that male endurance athletes carve out from their experiences of ageing and performance decline in the Nordic context. We conclude that current theorising of athletic career disregards the subjective career of the athlete and might not reflect careers especially in non-professional and veteran sports.